OPPORTUNITIES AND CHALLENGES FOR CLOUD COMPUTING (International Journal of Engineering and Computer Science, 2017)
Cloud computing is a new way of delivering computing resources and services. Cloud computing moved away from personal computers and the individual enterprise application server to services provided by the cloud of computers. The emergence of cloud computing has made a tremendous impact on the Information Technology (IT) industry over the past few years. Currently IT industry needs Cloud computing services to provide best opportunities to real world. Cloud computing is in initial stages, with many issues still to be addressed. This paper is a readings on “cloud” computing and it tries to address, related research topics, challenges ahead and possible applications.